2016
DOI: 10.17265/2328-2185/2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Is “Happy Worker” More Productive

Abstract: The hypothesis "happy productive worker" states that happy employees, whose needs are satisfied in their workplace, have greater performance than unhappy employees. Therefore, the purpose of this research is to examine empirically the effects that job satisfaction and well-being at work generate on the individual job performance, investigating the moderating role that the components of the organizational structure play in this relationship. To achieve the main objective, some secondary objectives were proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
1
5
0
1
Order By: Relevance
“…The Glassdoor indexes as a metric to assess employee happiness, expressing whether this is a good company to work for -overall satisfaction, career development, compensation and benefits, work/life balance, senior management, and CEO approval -comprise related factors to the concepts of well-being at work and job satisfaction. Thus, presenting the concept of happiness by joining the aspects of these two concepts is of great academic relevance, as it corroborates the approach to happiness that is widely used in the literature, such as the studies by Fisher (2010), andCoelho Junior (2016), among others. Furthermore, happiness is observed empirically in companies from different sectors, to make the analyzes applicable to different realities.…”
Section: Introductionsupporting
confidence: 59%
“…The Glassdoor indexes as a metric to assess employee happiness, expressing whether this is a good company to work for -overall satisfaction, career development, compensation and benefits, work/life balance, senior management, and CEO approval -comprise related factors to the concepts of well-being at work and job satisfaction. Thus, presenting the concept of happiness by joining the aspects of these two concepts is of great academic relevance, as it corroborates the approach to happiness that is widely used in the literature, such as the studies by Fisher (2010), andCoelho Junior (2016), among others. Furthermore, happiness is observed empirically in companies from different sectors, to make the analyzes applicable to different realities.…”
Section: Introductionsupporting
confidence: 59%
“…Empirical results from the study of the relationship between well-being and performance have suggested that moderating variables may affect the strength of this relationship (Fogaça & Coelho, 2016; Rego, 2009; Warr, 2007). These moderating factors can include organizational and job-related characteristics that together can affect organizational outcomes (Baron & Tang, 2011; N.…”
Section: The Moderating Role Of the Work Pattern And Office Type Fit mentioning
confidence: 99%
“…To explain these mixed results, researchers (Rego, 2009;Warr, 2007) suggest that moderating variables may affect the strength of the relationship between well-being and performance. This assumption is supported by empirical results indicating that there can be moderators in the well-being-performance relationship (Fogaça & Coelho, 2016), although research in this area is still scarce (Chi, Chang, & Huang, 2015).…”
mentioning
confidence: 92%
“…Mientras unos autores argumentan y encuentran que el bienestar se relaciona con el desempeño (Fogaça & Coelho-Junior, 2016;Wright, Larwood y Denney, 2002), otros llaman la atención sobre el hecho de que esto no siempre sucede (Youssef y Luthans, 2007). Estas contradicciones no son nuevas en la literatura, pero parecieran deberse más a discrepancias en la forma como se operacionaliza y mide el constructo que a resultados realmente contradictorios.…”
Section: Felicidad Y Trabajounclassified